Understanding ocean stratification and its interannual variability in the northeastern Chukchi Sea - Zhang, Jiaxu; Cheng, Wei; Stabeno, Phyllis; Veneziani, Milena; Weijer, Wilbert; McCabe, Ryan M. (Frontiers in Marine Science, 2024)
Ocean stratification on Arctic shelves critically influences nutrient availability, essential for primary production. However, discerning the changes in stratification and their drivers is challenging. Through the use of a high-resolution ocean-sea-ice model, this study investigates the variability in stratification within the northeastern Chukchi Sea over the period from 1987 to 2016. Our analysis, validated against available observations, reveals that summers with weak stratification are marked by a warmer water column that features a saltier upper layer and a fresher lower layer, thereby diminishing the vertical density gradient. In contrast, summers with strong stratification are characterized by a cooler column with a fresher upper layer and a saltier lower layer, resulting in an increased density gradient. This variability is primarily driven by the timing of sea-ice retreat and the consequent variations in meltwater flux, with early retreat leading to less meltwater and saltier surface conditions. This factor significantly outweighs the influence of changes in circulation and associated lateral freshwater transport driven by the Bering Strait inflow. We also find that the synchronization of sea-ice retreat and Bering Strait inflow intensity is linked to the timing and strength of the Aleutian Low's westward shift from the Gulf of Alaska to the Aleutian Basin in the early winter. These insights are crucial for understanding nutrient 1 Zhang et al.dynamics and primary production in the region. Furthermore, monitoring sea-ice retreat timing could serve as a useful proxy for predicting subsequent summer stratification changes.